Asymptomatic brain abscess following decompressive craniotomy for stroke – A report of two cases and review of the literature - Kutty, Raja; Sreemathyamma, Sunilkumar; Sivanandapanicker, Jyothish; Vijayan, Abhishek; Asher, Prasanth; Peethambaran, Anilkumar (Asian Journal of Neurosurgery, 2020)
Stroke is a significant health problem in both developed and developing nations. The treatment strategies of stroke differ among various centers depending on the available expertise. Nevertheless, stroke contributes to a major economic burden for patients and health institutions. The recovery period after stroke is a critical period wherein various complications can develop in survivors. Among these multiple complications, the formation of brain abscess in the infarcted brain tissue is rare and less well described in the literature. Fever or signs of raised intracranial pressure are the usual manifestation of poststroke brain abscess. We present two unique cases of large brain abscess in patients who survived a malignant stroke. Both the patients were recuperating well after decompressive craniectomy for stroke without any signs of intracranial infection or raised intracranial pressure. Both the patients underwent open drainage of brain abscess, followed by delayed cranioplasty. There are only a few cases of brain abscess reported in the literature in patients who underwent decompressive craniectomy for stroke.
Keywords: Brain abscess; cerebral infarction; decompressive craniectomy